2015
DOI: 10.5812/ircmj.25919
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure and Anxiety in Cancer Patients

Abstract: Background:Anxiety has negative effects on mental and physical performance, quality of life, duration of hospitalization, and even on the treatment of patients with cancer.Objectives:Today acupressure is widely used to treat anxiety. Thus, the present study aimed to investigate the effects of acupressure on anxiety in patients with cancer.Patients and Methods:A double-blind randomized clinical trial was conducted on 85 patients hospitalized with 3 groups including acupressure group (n = 27), sham group (n = 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
(46 reference statements)
0
18
1
Order By: Relevance
“…It may be also noted that the very high level of trait anxiety was not observed in patients with stomach cancer. This is in contrast with the literature, which associates gastric cancer with increased prevalence of anxiety and depressive symptoms in patients (19) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It may be also noted that the very high level of trait anxiety was not observed in patients with stomach cancer. This is in contrast with the literature, which associates gastric cancer with increased prevalence of anxiety and depressive symptoms in patients (19) .…”
Section: Discussioncontrasting
confidence: 99%
“…Research indicates that anxiety in cancer patients may be related to a multitude of reasons: as a response to the diagnosis of malignant neoplasm, long-term treatments, side effects of therapy, poor adherence to treatment, frequent hospitalizations, changes in the normal pattern of life, decreased quality of life, possible disfigurement, possibility of death, financial and social issues, and even the absence of family members during treatment/hospitalization (2,9,(17)(18)(19) . Other studies have shown a strong relationship between the family and the state of health and illness of their hospitalized members: that is, the family is extremely important in maintaining the health at all times of treatment, helping the patient to overcome feelings of anxiety (6,17,19,20) . Therefore, the absence of a family companion may have been one of the contributing factors to trait anxiety and state anxiety in moderate levels of the study participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupressure stimulation may also modulate the balance between the sympathetic and parasympathetic components of the autonomic nervous system; this plays an important role in repair mechanisms and maintenance of homeostasis, which in turn is implicated in many chronic diseases. [3][4][5] Before and after surgery, it has been reported that acupressure reduces musculoskeletal pain, especially of the head, neck and back, and alleviates many other symptoms such as fatigue, nausea, vomiting and itching. It may also reduce the dose requirements of drugs and has therefore become a popular treatment option in oncology, though there are a limited number of academic studies in this area.…”
mentioning
confidence: 99%
“…2 Finally, Beikmoradi et al recommended acupressure as a complementary therapy to reduce anxiety in cancer patients because of its low cost, safety and simplicity. 5 In summary, complementary approaches are being increasingly used in patients with cancer. Acupressure may release muscular tension, promote circulation of blood, and thereby relieve pain, strengthen immunity and promote healing.…”
mentioning
confidence: 99%